Body Percussion: Active and inclusive teaching oriented to disciplinary knowledge and transversal skills - Antinea Ambretti; Mariapia Mazzella; Wouter Cools (Excellence and Innovation in Learning and Teaching)
Body Percussion can be an innovative method to develop various motor and cognitive skills. Can promote inclusion in education without neglecting soft skills. This type of activity favours the inclusion of all, especially disabled pupils who, being able to work as au pairs, can feel part of a group by increasing their self-esteem, with positive effects on group dynamics.